THE ANALYSIS OF ENGLISH IDIOMS USING PART OF THE BODY IN NOVEL “THE ADVENTURES OF TOM SAWYER” BY MARK TWAIN AND THEIR IDIOMATIC TRANSLATION INTO INDONESIAN - Wirastuti, I Gusti Agung Putri (IKIP SARASWATI TABANAN, 2021)
According to Larson (1984) there are two kinds of translation, they are literal and idiomatic translation. Literalism can only be avoided by carefully analysis of the source language (SL) understanding clearly the message to communicate. Idiomatic translations use the natural forms of the receptor language (RL) and the basic overriding principle is that an idiomatic translation reproduces the meaning of the SL. Nida (1974) states that translating consist in reproducing in the receptor language the closest natural equivalent of the message, first in meaning and secondly in term of style or it is called Dynamic Equivalent. Both theories are applicable to analyze the data which are collected from bilingual novel from Mark Twain “The Adventures of Tom Sawyer” and in Indonesian from Abdoel Moeis “Tom Sawyer”. The analysis of the data is presented descriptively, in order to find the English Idioms using part of the body include the word ear, eye, face, hand, heart, head, nose, and tongue